Violence in Extreme Conditions Ethical Challenges in Military Practice - Kramer, Eric-Hans; Molendijk, Tine (Springer Nature, 2023)
As an organization operating under extreme conditions, the military is often confronted with destructive behavior from individuals, organizations, and societies. Written by experts from a variety of disciplines, this open access book reflects on confrontations with violence under extreme conditions and the various challenges that arise. By examining real first-hand accounts of soldiers' deployments, the contributions shed new light on the multifaceted and sometimes hidden dynamics of destructive violent behavior and offer an ethical reflection on military practices. In addition, they address topics such as moral decision-making in violent contexts, military trauma, organizational change, and military ethics education. The interdisciplinary exploration of these topics has been the primary focus of Désirée Verweij, who was the Chair of Military Ethics at the Netherlands Defence Academy from 2008 to 2021. The contributions in this book are written in honor of her scholarly achievements and help to ensure that these important issues continue to receive attention. The book will appeal to scholars of military studies, organizational studies and military ethics, and to professionals and decisionmakers in military organizations.